Deficient RNA-editing enzyme ADAR2 in an amyotrophic lateral sclerosis patient with a FUSP525L mutation. (October 2016) - Aizawa, Hitoshi; Hideyama, Takuto; Yamashita, Takenari; Kimura, Takashi; Suzuki, Naoki; Aoki, Masashi; Kwak, Shin
Highlights: We describe a patient with juvenile-onsent amyotrophic lateral sclerosis (ALS) with a FUS P525L mutation. This case demonstrates ADAR2 deficiency and FUS-positive cytoplasmic inclusions. ADAR2 deficiency can occur unrelated to the presence of FUS-positive inclusions. FUS-associated ALS may share neurodegenerative characteristics with classical sporadic ALS. Abstract: Mutations in the fused in sarcoma ( FUS ) gene can cause amyotrophic lateral sclerosis (ALS), and FUS gene mutations have been reported in sporadic ALS patients with basophilic cytoplasmic inclusions. Deficiency of adenosine deaminase acting on RNA 2 (ADAR2), an enzyme that specifically catalyzes GluA2 Q/R site-editing, has been reported in considerable proportions of spinal motor neurons of the majority of sporadic ALS patients. We describe the relationship between GluA2 Q/R site-editing efficiency and FUS-positive inclusions in a patient with FUS P525L . A 24-year-old woman with ALS presented with basophilic cytoplasmic inclusions, significantly reduced GluA2 Q/R site-editing efficiency in the spinal motor neurons, and markedly decreased ADAR2 mRNA levels. Neuropathologic examination showed that not all spinal motor neurons expressed ADAR2 and revealed FUS-positive cytoplasmic inclusions in motor neurons irrespective of ADAR2 immunoreactivity. There were no phosphorylated transactive response (TAR) DNA-binding protein 43 kDa (TDP-43)-positive inclusions, indicating that there was no tight correlation between ADAR2 deficiency and TDP-43 deposition. ADAR2 deficiency can occur in ALS patients with a FUS P525L mutation and is unrelated to the presence of FUS-positive inclusions. FUS-associated ALS may share neurodegenerative characteristics with classical sporadic ALS.